Neurophysiological Testing in Normal Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators in Belgrade, Serbia, and Newcastle upon Tyne, UK, reviewed the literature (Ovid Medline, 1948-2012) for citations on repetitive nerve stimulation (RNS) and single fiber electromyography (SFEMG) in children.